Digital Christianity: how digitalization affects the Christian beliefs and practices of young people - Choong, Wayne Wen Tai (Nanyang Technological University, 2023)
Religion holds sway over more than 85% of the global population, but the advent of digitalization has disrupted the way many individuals experience and practice religion. This disruption has given rise to the emerging field of digital religion, which explores the intersection of technology and religious identity. However, the relationship between Christian youths and digitalization in Singapore has not yet been the subject of sufficient academic research, despite the fact that today's youth are often considered digital natives. Therefore, investigating the Singaporean church is crucial to filling the gaps in the literature on digital religion in Southeast Asia. Through extensive original field research and digital textual analysis, this ethnographic study examines Digital Christianity in Singapore, specifically focusing on the impact of digitalization on the beliefs and practices of Christian youths. By doing so, this research makes significant contributions to the fields of digital religion and sociology of religion. The data collected reveals that young people's religious identities evolve within an ecosystem of direct and indirect digitalisation. Indirectly, their Christian beliefs and practices change with the digitalization of faith-based communities and religious authority. Directly, the digitalisation of their beliefs and practices and its effects are most noticeable in their use of social media and communication apps. This study also adopts an interpretive approach, introducing the concept of "spiritualization" as a framework for analyzing the social construction process through which digital religion, its practices, and accompanying beliefs are developed and embraced. Additionally, the COVID-19 pandemic and its associated restrictions have accelerated the process of digitalization, further emphasizing the significance of digital Christianity. This unique context provides an exceptional opportunity to observe the spiritualization and reconstruction of core Christian elements. Holistically, this research offers valuable insights into the far-reaching implications of an increasingly digitalized world, where the realm of religion is not exempt from profound transformations. By examining the impact of digitalization on Christianity, the church, and its followers, it uncovers a dynamic and fluid landscape shaped by the pervasive influence of digital culture.